2018
DOI: 10.1186/s12885-018-4559-3
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: p300 promotes proliferation, migration, and invasion via inducing epithelial-mesenchymal transition in non-small cell lung cancer cells

Abstract: BackgroundHistone acetyltransferase p300 is a crucial transcriptional coactivator and has been implicated as a poor prognostic factor in human cancers. However, little is known about the substantial functions and mechanisms of p300 in NSCLC proliferation and distant metastasis.MethodsWe constructed p300 down-regulated and up-regulated cell lines through RNAi and recombinant plasmid transfection. Cell Counting Kit-8 assays were used to test the cell proliferation and confirmed by colony formation assays. Wound … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 23 publications
3
32
0
Order By: Relevance
“…In agreement with ndings that EP300 increases migratory potential and invasiveness of cancer cells [39], [40], we demonstrated reduced lung colonization and distant metastasis as well as circulating tumor cells via EP300 KD in TNBC cells.…”
Section: Discussionsupporting
confidence: 92%
“…In agreement with ndings that EP300 increases migratory potential and invasiveness of cancer cells [39], [40], we demonstrated reduced lung colonization and distant metastasis as well as circulating tumor cells via EP300 KD in TNBC cells.…”
Section: Discussionsupporting
confidence: 92%
“…[ 27 ] EP300 has been proved to be upregulated in several malignancies, such as non-small cell lung cancer, colorectal carcinomas, hepatocellular carcinoma. [ 28 30 ] A recent study demonstrated that mutation of EP300 is correlated with higher tumor mutation burden (TMB) and promotes antitumor immunity in bladder cancer patients. [ 31 ] Dou et al [ 32 ] showed that phosphorylation of EP300 associated with liver metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have demonstrated p300 was associated with enhanced EMT and correlates with poor prognosis in these cancers [41,43]. Overexpression of p300 promotes cell proliferation, migration, and invasion in NSCLC cells [42]; knockdown of p300 inhibited EMT, invasion and other malignant events of HCC cells [43]. However, we must note that p300 may act as a suppressor of tumor metastasis in some cancers.…”
Section: Discussionmentioning
confidence: 89%
“…Abnormal expression of p300 has been identi ed in esophageal squamous carcinoma, NSCLC cells and hepatocellular carcinoma [41][42][43]. Numerous studies have demonstrated p300 was associated with enhanced EMT and correlates with poor prognosis in these cancers [41,43].…”
Section: Discussionmentioning
confidence: 99%